STUDI TENTANG NILAI-NILAI PANCASILA DALAM TRADISI REWANG SUKU JAWA DI KAMPUNG BUANA MAKMUR KECAMATAN DAYUN - Ninik Sugiarti; Hambali Hambali; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is moivaed by Pancasila is an Indonesian national idiology in carrying out the life of nation and state. Where the whole community is guided by the Pancasila itself. In the meaning of Pancasila it is stated that all components in the life of the nation and state must practice the mandate of the values contained in the Pancasila itself startung from how to live the context of individuals and groups. One of which is in the tradition of Javanese ribal Rewang. For example in terms of mutual cooperation and a sense of solidarity in the tradition of the Rewang is one of deeds of the values of the Pancasila. The formulation of the problem in this study is whether there are Pancasila values in the tradition of the Javanese tribe Rewang in Kampung Buana Makmur Kecamatan Dayun Kabupaten Siak. As for the purpose of this study is to find ou the pancasila in the tradition of the Javanese tribe Rewang in Kampung Buana Makmur Kecamatan Dayun Kabupaten Siak. While the sampling toechnique used a purposive sampling toechnique that is as many as 18 families from Javanese tribes who understand and have criteria about the tradition of Rewang in Kampung Buana Makmur. Data collection techniques are observasion, questionnaire, interview, and documenaion. Data analysis techniques used in this study are descriptive qualitative with formula P=f/n X 100%. The results showed that data on the Javanese Rewang Tradition were known to be 97.7% stated YES and 2.3% stated NO. Based on the benchmarks that answer "Yes" that is 97.7% are in the range of 50.01% - 100% or "Exist". So in this study it is evident that the Javanese Rewang Tradition in Buana Makmur, Dayun District, Siak Regency Contains Pancasila Values.Keywords: Pancasila’s Values, Rewang Javanese Tradition